Prediksi Kebangkrutan Pada PT Sepatu Bata Tbk Berdasarkan Rasio Keuangan Menggunakan Metode Altman Z-Score Periode 2014–2024 - Ahmad Fahrudin; Tri Sulistyani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to analyze the financial health and predict the bankruptcy potential of PT Sepatu Bata Tbk based on financial ratios using the Altman Z-Score method during the 2014–2024 period. The research employs a descriptive quantitative approach using secondary data in the form of the company’s audited annual financial statements. The analysis is conducted by calculating five financial ratios that form the Altman Z-Score model, namely Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Taxes to Total Assets, Market Value of Equity to Total Liabilities, and Sales to Total Assets. The results show that the Z-Score of PT Sepatu Bata Tbk has a minimum value of −0.42, a maximum value of 6.18, an average of 3.62, and a standard deviation of 2.16. Periodically the company was in a non-distress condition during 2014–2019, entered the grey zone in 2020 and 2022, and experienced financial distress in 2023 and 2024. These conditions indicate that PT Sepatu Bata Tbk faces an increasing risk of bankruptcy at the end of the observation period.